Scripta Medica, Volume 51, 2020: a Short Overview - Stojiljković, Miloš P (Scripta Medica, 2020)
This editorial presents the analysis of volumes 50 (2019) and 51 (2020) of Scripta Medica. Original articles made 53 % of 80 articles published in these two volumes. Article rejection rate was 38 %. Mean duration of period until reaching the first decision on an article was 20 days, while mean time until reaching the final decision was 31 days. Mean time needed for accepting the revised manuscript was 3 days, reflecting a significant decrease from 5 days in 2019 to 2 days in 2020. Mean time needed for reaching a decision to reject an article was 7 days. Coverage of the journal included both basic and clinical research and a considerable space was devoted to articles on COVID-19. Further efforts will be made in order to reach a more international recognition of the journal.